A efetivação de medidas estruturantes pelo Supremo Tribunal Federal em processos de competência originária - Frajdenberg, Charles Pachciarek (2022)
In a country still full of social inequalities, great concentration of wealth, with public policies failing to implement social rights, collective disputes of irradiated diffusion that affect fundamental rights of discrete and insular minorities are common. Structural processes of original jurisdiction are already being processed in the Federal Supreme Court, originated through allegations of non-compliance with a fundamental precept, for intervention in public policies that demean the human rights of these marginalized groups. These are dialogic processes, through extensive debate and participation of various groups involved, in which the main requests are the elaboration of plans by the defendants so that the public policy considered precarious, obstructed from progress, in the face of deliberative blocks of the other powers, be overcome through the redesign of institutions. The objective is to move from a non-ideal state of affairs to a situation of normality. In other words, the Court will function as a true promotional center of synergy to overcome the unconstitutional state of affairs in search of positive holistic results from advances in dormant and inefficient public policy. The phase of monitoring overcoming plans to unblock flawed public policies is the most important, being the longest and different from what we are used to in ordinary civil proceedings. The Constitutional Court will have to rethink traditional practices of orthodox civil procedure, adapting it and incorporating new practices, in the light of the experiences of countries such as the United States, Colombia and South Africa, for example. How this program-process will develop and become effective, reviewing basic principles and institutes of traditional civil procedure, is a great challenge and object of the present study. The method used is deductive, through bibliographic research in national and foreign books and periodicals.